1994
DOI: 10.1177/0310057x9402200602
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Outcome following Cardiopulmonary Resuscitation

Abstract: Many patients who receive cardiopulmonary resuscitation (CPR) for cardiac arrest do not survive to leave hospital. Factors associated with adverse outcomes include unwitnessed cardiac arrest in general wards, particularly at night, prolonged resuscitation, asystole, associated disorders (e.g. sepsis, malignancy, renal failure, and left ventricular dysfunction), absent pupillary responses, hypoxaemia, low PetCO2 during resuscitation, and severe acid base imbalance. Outside hospitals, cardiac arrests result in m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
11
0
1

Year Published

1997
1997
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(12 citation statements)
references
References 122 publications
0
11
0
1
Order By: Relevance
“…There is only one study that discussed the number of cardiac arrests that the patient experienced before and its effect on the outcome of CPR, and they found that it was not a significant factor; 24 this agrees with the present study findings.…”
Section: Discussionmentioning
confidence: 99%
“…There is only one study that discussed the number of cardiac arrests that the patient experienced before and its effect on the outcome of CPR, and they found that it was not a significant factor; 24 this agrees with the present study findings.…”
Section: Discussionmentioning
confidence: 99%
“…This demonstrates a specific, but not very sensitive, indicator of survival and suggests that pooling several variables may be helpful in predicting outcome. These findings also suggest that neurological function is a very important determinant of outcome and that more sensitive neurophysiological testing might be a useful prognostic tool [3,13].…”
Section: Discussionmentioning
confidence: 83%
“…The prognosis of patients who survive the initial resuscitation after a cardiac arrest is often thought to be poor, in terms of both mortality and morbidity [1][2][3]. However, there is little published work from the United Kingdom to confirm or refute this view.…”
mentioning
confidence: 99%
“…After an acute drug poisoning leading to cardiac arrest and successful resuscitation, low blood glucose levels were measured using capillary blood in four patients, two pre‐hospitally and two in the ED. Hyperglycaemia, rather than hypoglycaemia, is a common finding in patients resuscitated from cardiac arrest (19–22). Morphine’s ability to induce hyperglycaemia in humans has been reported previously (23).…”
Section: Discussionmentioning
confidence: 88%